Land redistribution, tenure insecurity, and intensity of production: a study of farm households in southern Ethiopia - Holden, Stein; Yohannes, Hailu (International Food Policy Research Institute, 2001)
This study analyzes the determinants of land tenure insecurity and its impact on intensity of use of purchased farm inputs among households in Southern Ethiopia. Seventeen percent of the households stated that they were tenure insecure. The feeling of tenure insecurity could be caused by the land redistribution policy in Ethiopia where household size has been the main criterion used for land allocation after the land reform in 1975. This would imply that land rich households should be more tenure insecure. Alternatively, the local power structure may be strong enough to counter this and cause the land rich, who are also likely to be influential, to be able to protect their land rights. The analysis revealed that, in the overall sample, relative farm size was not significantly correlated with tenure insecurity. When testing for each site, however, we found that in four of the sites per capita farm size was positively associated with tenure insecurity, while in five other sites it had a significant negative association. This may be due to local historical, cultural, and demographic differences giving way to differences in the effects of the redistribution policy and the local power structure on tenure insecurity. We assessed the impact of tenure insecurity on the intensity of use of purchased farm inputs. The tenure insecurity variable was insignificant. Farmers in areas with a positive correlation between farm size and tenure insecurity were more likely to purchase farm inputs. Larger farms were more likely to use purchased inputs, but this effect was lower in areas with a positive correlation between farm size and tenure insecurity. Poverty and subsistence constraints may explain this absence of higher intensity of use of purchased inputs on small farms. By contrast, the land redistribution policy may have improved small farms' access to purchased farm inputs. (text of Abstract)